Cochlear implant and autism spectrum disorder: a case report - Vanessa Luisa Destro Fidêncio; Valéria Figueiredo Madureira; Tatiana Medeiros Deperon; Flávia Melo Mundim; Anacleia Melo da Silva Hilgenberg; Camila da Costa Ribeiro (Revista CEFAC, 2023)
ABSTRACT Autism Spectrum Disorder is not an adverse condition for cochlear implantation, but the goals and expectations about the effects on hearing and language outcomes are different from the group of children without other impairments. The objective of this study was to analyze the development of auditory and oral language skills of a child with autism who underwent early cochlear implantation surgery and was included in an auditory (re)habilitation program using the aural-oral method. There was no benefit from the device for the development of oral language, and the child was referred to another communicative method. After 2 years and 9 months using the cochlear implants, there was little benefit from the use of the device for the development of auditory skills, with the child evolving to recognize only his own name. The patient quit using the device after three years of its activation.